2001
DOI: 10.1093/bja/87.6.848
|View full text |Cite
|
Sign up to set email alerts
|

Safety of oral nicorandil before coronary artery bypass graft surgery

Abstract: Nicorandil is a K(ATP) channel opener used to treat angina. It is cardioprotective and a vasodilator. We conducted a prospective, randomized, double-blind, placebo-controlled study to assess oral nicorandil in patients undergoing coronary artery bypass grafting (CABG) with cardiopulmonary bypass (CPB). Twenty-two patients received nicorandil (10 mg twice a day) and 23 patients received placebo. Haemodynamic data were recorded before induction of anaesthesia (T0), 5 and 20 min after starting mechanical ventilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
2
1
0
Order By: Relevance
“…On the other hand, Blanc P. and his colleagues in their study; concluded that no statistically important variance between placebo group and nicorandil group on cardiac enzymes release and hemodynamic variables in patients undergoing CABG surgery. The authors assumed that nicorandil, was safe for usage as a medication but there was uncertainty about its cardio protective result [24]. We agree with Blanc P. and as regard the safe use of nicorandil but there is a controverse as regard the levels of post-operative myocardial enzymes concentration.…”
Section: Discussionsupporting
confidence: 60%
“…On the other hand, Blanc P. and his colleagues in their study; concluded that no statistically important variance between placebo group and nicorandil group on cardiac enzymes release and hemodynamic variables in patients undergoing CABG surgery. The authors assumed that nicorandil, was safe for usage as a medication but there was uncertainty about its cardio protective result [24]. We agree with Blanc P. and as regard the safe use of nicorandil but there is a controverse as regard the levels of post-operative myocardial enzymes concentration.…”
Section: Discussionsupporting
confidence: 60%
“…Previous research has shown that both preoperative and intraoperative administration of NICD could have a positive impact on patient outcomes. [23][24][25] In our study, perioperative use of NICD has shown to exert a myocardial protective effect indeed. In addition, the subgroup analysis with preoperative NICD showed a new role of NICD in liver protection.…”
Section: Discussionsupporting
confidence: 58%
“…However, Belhomme et al failed to show a benefit [37]. Nicorandil also did not consistently prove to be useful when used during coronary bypass surgery [38,39]. None of these conditioning mimetic drugs are now being utilized routinely in conjunction with on-pump coronary bypass surgery.…”
Section: Preconditioning and Coronary Artery Bypass Surgerymentioning
confidence: 99%